PERAN ORANG TUA DALAM MELINDUNGI HAK ANAK - Hutabarat, Dany Try Hutama; Wahyuni, Sri; Anggraini, Sustika Winda; Khulsum, Umi; Saputri, Eliana; Syahputra, Heri; Zahari, Yusri; Salsabilla, Rinia; Kinanti, Sri; Sulistia, Irma (Transpublika Publisher, 2022)
This study aims to find out the role of parents to protect children. The type of method used in this study is normative method. The system of norms in question is about the principles, norm rules, of laws and regulations, court decisions, agreements and doctrines (teachings). The results showed that special protection is the protection provided to children in emergency situations, children facing the law, children from minority and isolated groups, children who are economically exploited, the lack of education of children who are victims of drug abuse, alcohol, psychotropic, and other addictive substances, children victims of kidnapping, sales, trafficking, children victims of both physical and mental abuse, children with disabilities, and children victims of wrong treatment and neglect. The tasks of development that start from infancy are social expectations, including learning to walk, eating solid food, controlling disposal devices, achieving good physical stability, speech exercises and emotionally related to parents and siblings and people who were nearby to different degrees when born.